Issues And Challenges Of Corporate Change Initiatives In Singapore's Small Business Sector - Menkhoff, Thomas; Loh, Benjamin; Kay, Lena (Asian Academy of Management (AAM), 2003)
This paper1 explores the change propensity of owners of small and medium-sized enterprises (SMEs) and associated challenges in the Republic of Singapore. Based on both qualitative interviews and quantitative survey research amongst Singapore's SME owners and change advocates, it identifies several critical issues with regard to the successful management of organizational transitions in small firms: "the need to change", "the mindset of small entrepreneurs", "change management know how" and "the value of external consultancy inputs". The data suggest that awareness building measures and educational efforts are necessary to enable more owners of local SMEs to benefit from change management tools and concepts as well as respective external expertise. Change management training and exposure to "best" (sectoral) change management practices and successful projects facilitated by external change agents might help more small entrepreneurs to manage both intra-organizationally and externally induced organizational changes more effectively.